Acheiropoietes – mimesis doskonała? - Zawadzki, Andrzej (Wydawnictwo Naukowe UAM, 2014)
The paper deals with the topic of an acheiropoietes (an image “not made by hands”) and, more broadly, with the motif of the so-called true or natural image. Such images were known to ancient Greek thinkers (Dionysius of Halicarnassus and Plotinus), but their importance grew significantly in the Christian theology of icons which treated Christ as the perfect image of His Father. In modern times true images mostly function in folklore and they are also referred to in modern art. From the perspective of the philosophy of representation, a true image is an interesting utopia of perfect mimesis – it comes into being in a natural, not artificial way, whereas a copy is regarded as equivalent to the original.
Acheiropoietes – perfect mimesis?